Odpowiedź:
a)
[tex]P_c = Pb + 2 * Pp\\\\P_p = ab\\P_b = 2 * ah + 2 * bh\\\\P_p = 7 * 7 = 49\\P_b = 4 * (7 * 13,5) = 378\\P_c = 378 + 2 * 49 = 476cm^2[/tex]
b)
[tex]P_c = Pb + 2 * Pp\\\\P_p = ab\\P_b = 2 * ah + 2 * bh\\\\\\a = 3,5dm = 35cm\\b = 120mm = 12cm\\c = 0,04m = 4cm\\\\P_p = 35 * 12 = 420\\P_b = 2 * (35 * 4) + 2 * (12 * 4) = 376\\P_c = 420 + 2 * 376 = 1172cm^2 = 11,72m^2[/tex]
c)
[tex]P_c = Pb + 2 * Pp\\\\P_p = ab\\P_b = 2 * ah + 2 * bh\\\\a = \frac{1}{4} * 2 = 0,5cm\\b = 5,4cm\\c = \frac{2}{3} * 6 = 4cm\\\\P_p = 0,5 * 5,4 = 2,7\\P_b = 2 * (0,5 * 4) + 2 * (5,4 * 4) = 47,2\\P_c = 47,2 + 2 * 2,7 = 52,6cm^2[/tex]
Szczegółowe wyjaśnienie: